Cortical and amygdalar neuronal ensembles in alcohol seeking, drinking and withdrawal. (1st August 2017) - George, Olivier; Hope, Bruce T.
Abstract: Alcohol induces many alterations in the brain that are thought to contribute to alcohol addiction. Most of the known alterations are induced in all neurons of a brain area or all neurons of a given cell type, regardless of whether they were activated during behavior. While these alterations can have important modulatory effects on behavior, they cannot explain why animals respond specifically to alcohol-paired cues as opposed to all other non-paired cues and evoke highly specific goal-directed learned responses in models of drug craving. As an alternative, we hypothesize another class of alterations that are induced only within sparsely distributed patterns of neurons, called neuronal ensembles, that are selectively activated by alcohol-specific cues during behavior and encode the long-term memories underlying these learned behaviors in animal models of alcohol addiction. Here we review recent studies and techniques used to identify the role of neuronal ensembles in animal models of different phases of the alcohol addiction cycle. This article is part of the Special Issue entitled "Alcoholism". Highlights: Novel approaches to study the neuronal ensembles of alcoholism. A neuronal ensemble in the infralimbic cortex prevents relapse in dependent rats. A neuronal ensemble in the central amygdala promotes drinking in dependent rats. Remaining questions on the timing and consolidation of ensembles are highlighted. A hypothesis on how these neuronal ensembles may interact is proposed.